Harrison's endocrinology - Jameson, J. Larry (McGraw Hill Medical, 2010)
Featuring the chapters on endocrinology, this clinical companion includes coverage of need-to-know endocrinology topics, including pituitary, thyroid, and adrenal disorders; reproductive endocrinology; diabetes mellitus, obesity, and lipoprotein metabolism; and disorders affecting multiple endocrine systems.